PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PT. VAGABOND SOLUSI INDONESIA - I G NG A Gede Eka Teja Kusuma; Ni Putu Nita Anggraini; Dhea Chandra Kirana (VALUES, 2024)
This study aims to analyze the influence of organizational culture, work discipline and motivation on employee performance at PT. Vagabond Solutions Indonesia. This type of research is quantitative, the population in this study is all employees at PT. Vagabond Solusi Indonesia totaled 32 people. The sampling technique used is the Saturated Sampling Technique, where all populations in this study are sampled. The data analysis technique used is multiple linear regression analysis. The results showed that organizational culture, work discipline and motivation had a significant positive effect on employee performance at PT. Vagabond Solutions Indonesia. The researcher suggested to the next researcher that they could develop research in terms of adding independent variables, where this step was carried out with the aim of providing other influences when testing dependent variables or employee performance variables. Variables that can be suggested include: suitability of compensation, work environment, internal control system and others.